2018
DOI: 10.1007/s00109-018-1717-7
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomal functions of phosphorylated and unphosphorylated STAT1 in hepatocellular carcinoma

Abstract: Interferons (IFNs) with antiviral and immune-stimulatory functions have been widely used in prevention and treatment of hepatocellular carcinoma (HCC). Signal transducer and activator of transcription 1 (STAT1) is a key element of the IFN signaling, and the function of STAT1 is critically determined by its phosphorylation state. This study aims to understand the functions of phosphorylated (p-) and unphosphorylated (u-) STAT1 in HCC. We found that u-STAT1 is significantly elevated in patient HCC tumor tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…In a recent study, the authors found that elevated expression of STAT1 without activation (i.e., unphosphorylated STAT1) was observed in HCC patients [68]. The presence of unphosphorylated STAT1 was able to sustain growth in HCC cell lines in vitro [68]. This is an important finding in guiding the development of drug targets against STAT1 as a therapeutic strategy.…”
Section: The Role Of Other Stats In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the authors found that elevated expression of STAT1 without activation (i.e., unphosphorylated STAT1) was observed in HCC patients [68]. The presence of unphosphorylated STAT1 was able to sustain growth in HCC cell lines in vitro [68]. This is an important finding in guiding the development of drug targets against STAT1 as a therapeutic strategy.…”
Section: The Role Of Other Stats In Hccmentioning
confidence: 99%
“…Notably, the antitumorigenic properties of STAT1 correlate with the activity of STAT1 instead of the expression levels of the protein itself. In a recent study, the authors found that elevated expression of STAT1 without activation (i.e., unphosphorylated STAT1) was observed in HCC patients [68]. The presence of unphosphorylated STAT1 was able to sustain growth in HCC cell lines in vitro [68].…”
Section: The Role Of Other Stats In Hccmentioning
confidence: 99%
“…Expression of mRNA in different samples were measured according to the manufacturer's instructions [25]. GAPDH was considered as reference gene for normalization.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…As members of the IRDS gene classifier, MCL1, IFIT3 and ISG15/G1P2 upregulation were associated with constitutive STAT1 overexpression . Blocking u‐STAT1 expression, but not p‐STAT1, was sufficient to resensitize cancer cells to IFNα's tumoricidal effects …”
Section: Roles Of Ifnα In Cancer Immunoeditingmentioning
confidence: 98%
“…IFNα transiently raises the amount of intracellular phosphorylated STAT1 (p‐STAT1), which declines over time to yield high levels of u‐STAT1. Both p‐STAT1 and u‐STAT1 are dichotomous phosphorylation states of the ISG protein STAT1 . Cytosolic u‐STAT1 was shown to induce transcription of a distinct subset of ISGs produced late in response to type I IFNs—including STAT1 itself—regardless of IFN activation or STAT1 phosphorylation .…”
Section: Roles Of Ifnα In Cancer Immunoeditingmentioning
confidence: 99%